Credit supply and human capital: Evidence from bank pension liabilities - Luciana Barbosa; Andrada Bilan; Claire Célérier (European Central Bank (ECB), 2019)
We identify the effects of exogenous credit constraints on firm ability to attract and retain skilled workers. To do so, we exploit a shock to the value of the pension obligations of Portuguese banks resulting from a change in accounting norms. Using bank-firm credit exposures that we match with a census of all Portuguese employees, we show that firms in a relationship with affected banks borrow less and reduce employment mostly of high-skilled workers. High-skilled workers are more likely to exit and less likely to join affected firms. Overall, credit market frictions might have long lasting effects on firm productivity and growth through firm accumulation of human capital.
Keywords: G21; J21; J24; 330; Credit Frictions; Employment; Skills; Wages